Global application of an unoccupied aerial vehicle photogrammetry protocol for predicting aboveground biomass in non‐forest ecosystems. Issue 1 (7th July 2021) - Cunliffe, Andrew M.; Anderson, Karen; Boschetti, Fabio; Brazier, Richard E.; Graham, Hugh A.; Myers‐Smith, Isla H.; Astor, Thomas; Boer, Matthias M.; Calvo, Leonor G.; Clark, Patrick E.; Cramer, Michael D.; Encinas‐Lara, Miguel S.; et al.
Abstract: Non‐forest ecosystems, dominated by shrubs, grasses and herbaceous plants, provide ecosystem services including carbon sequestration and forage for grazing, and are highly sensitive to climatic changes. Yet these ecosystems are poorly represented in remotely sensed biomass products and are undersampled by in situ monitoring. Current global change threats emphasize the need for new tools to capture biomass change in non‐forest ecosystems at appropriate scales. Here we developed and deployed a new protocol for photogrammetric height using unoccupied aerial vehicle (UAV) images to test its capability for delivering standardized measurements of biomass across a globally distributed field experiment. We assessed whether canopy height inferred from UAV photogrammetry allows the prediction of aboveground biomass (AGB) across low‐stature plant species by conducting 38 photogrammetric surveys over 741 harvested plots to sample 50 species. We found mean canopy height was strongly predictive of AGB across species, with a median adjusted R 2 of 0.87 (ranging from 0.46 to 0.99) and median prediction error from leave‐one‐out cross‐validation of 3.9%. Biomass per‐unit‐of‐height was similar within but different among, plant functional types. We found that photogrammetric reconstructions of canopy height were sensitive to wind speed but not sun elevation during surveys. We demonstrated that our photogrammetric approach produced generalizable measurements across growth forms and environmental settings and yielded accuracies as good as those obtained from in situ approaches. We demonstrate that using a standardized approach for UAV photogrammetry can deliver accurate AGB estimates across a wide range of dynamic and heterogeneous ecosystems. Many academic and land management institutions have the technical capacity to deploy these approaches over extents of 1–10 ha −1 . Photogrammetric approaches could provide much‐needed information required to calibrate and validate the vegetation models and satellite‐derived biomass products that are essential to understand vulnerable and understudied non‐forested ecosystems around the globe. Abstract : Working at sites across the globe, we used a standardized protocol to collect and analyse drone data in order to measure the size of many different plants in non‐forest ecosystems. These measurements of canopy height allowed the prediction of aboveground biomass and carbon storage of different plants accurately across the landscape. This new approach to measuring plants enables detailed monitoring of vegetation dynamics and responses to differences in climate or disturbance that can help us understand the changes happening in important and vulnerable non‐forest ecosystems around the world.